The Effect Of Leadership Style And Work Motivation On Employee Performance At Bank Rakyat Indonesia Cemara Unit - Rianda, Egy; Hasibuan, Hasrul Azwar (Jurnal Fokus Manajemen, 2025)
This study aims to determine the effect of leadership style and work motivation on employee performance at Bank Rakyat Indonesia Unit Cemara. In this study, the population used was all employees of Bank Rakyat Indonesia Unit Cemara with a total of 39 employees who are all administrative staff of PT. Reska Multi Usaha Medan in 2024. The research sample was 39 employees who were all employees of Bank Rakyat Indonesia Unit Cemara in 2024. The research was conducted in 2024. This study uses quantitative data processed using the SPSS version 24.0 application with a multiple linear regression model. The data source used is primary data taken directly from respondents. Data collection was collected by distributing questionnaires. The results of the study indicate that the work environment, work discipline and compensation have a positive effect. Leadership style has a positive and significant effect on the performance of Bank BRI Unit Cemara employees. This can be seen from the regression coefficient value of 0.395. The t-value is 4.291 with a significant value of 0.000 which is smaller than 0.05. Work motivation has a positive and significant effect on the performance of Bank BRI Unit Cemara employees. This can be seen from the regression coefficient value of 0.364. The t-value is 4.053 with a significant value of 0.000 which is smaller than 0.05. Leadership style and work motivation simultaneously have a positive and significant effect on the performance of Bank BRI Unit Cemara employees. This can be seen from the F-value of 85.178 with a significant value of 0.000 <0.05. Based on the results of the determination coefficient test, the R-square value is 0.826 or 82.6%. This means that the ability of leadership style and work motivation in this study is able to explain employee performance by 0.826 or 82.6%.